Traditional Birth Attendants’ Contribution to Maternal Health and Malaria Prevention in Ilorin Metropolis, Nigeria (Journal of Gender and Social Issues, 2025)
The study investigates the role of Traditional Birth Attendants (TBAs) in preventing malaria among pregnant women in Ilorin Metropolis, Nigeria, where TBAs are deeply rooted in local customs and handle a significant number of deliveries. Despite this, Nigeria faces high rates of maternal and infant mortality, highlighting gaps in the healthcare system, particularly in rural areas. Using a cross-sectional survey, 234 pregnant women who had utilized TBA services were studied, employing both structured questionnaires and oral interviews. Results show that most pregnant women (62%) reported TBAs referring women with complications to hospitals, indicating collaboration with modern healthcare. However, concerns exist about healthcare workers’ attitudes and the strained relationship between TBAs and healthcare facilities. Further exploration is needed to address these issues and redefine the roles of TBAs, emphasizing the importance of adequate supervision for their integration into the formal health system.
Keywords: Malaria; Maternal Health; Traditional Birth Attendants.